Inflammatory response after nailing. (June 2017) - Kanakaris, Nikolaos K.; Anthony, Christopher; Papasotiriou, Antonios; Giannoudis, Peter V.
Abstract: Intramedullary nailing, as the gold standard stabilisation method of most long bones, has been tailed by its extensive use as the basic tool of investigating the immune response to trauma in many large and small animal models, as well as at the clinical setting. Over the last few decades a complex map of interactions between pro and anti-inflammatory pathways has been the result of these significant global research efforts. Parallel to the evolution of modern nailing and reaming techniques, significant developments at the fields of other disciplines relevant to trauma care, has improved the contemporary management of injured patients, challenging previous concepts and altering clinical barriers. The current article aims to summarise the current understanding of the effect of instrumenting the medullary canal after trauma, and hint on potential future directions.